Women's Power in the Tradition of Menglolo Utang in Pakpak Ethnic Pre-Marriage Ceremony in Dairi, North Sumatra - Ratih Baiduri; Hesty Verawati Panjaitan (Universitas Negeri Medan, 2022)
The tradition of Menglolo Utang is a tradition practiced by Pakpak ethnic group before the marriage ceremony. This study aims to examine: (1) The background of the tradition of Menglolo Utang, (2) The process of implementing the tradition of Menglolo Utang in the Pakpak ethnic group and (3) The power of women (the bride's biological mother) in the tradition of Menglolo Utang. This type of research is descriptive qualitative with ethnographic approach. The theory used in this study is the theory of power relations from Foucault. The results of this study found that: (1) The background to the practice of Menglolo Utang in the Pakpak ethnicity was that married girls would be brought to the men's house. Therefore, it is the mother who has power over her daughter, (2) The process of carrying out the tradition of Menglolo Utang to the Pakpak ethnic group is the men visiting the house of the woman and discussing the number of gold (Sipihir-pihir) to the mother of the bride, (3) The bride's biological mother in the tradition of Menglolo Utang has the power to determine the number of Sipihir-pihir and decide whether her daughter can be proposed or not.